Promising lines of Eggplant (Solanum melongena) Developed through Population improvement of locally popular cultivar –Plastic - Arasakesary, S.J.; Amirthalojanan, A.; Gugapriya, R.; Yogeswaran, T. (University of Jaffna, 2019)
Recurrent selection is an important breeding method employed to improve the populations of crop plants particularly those of cross-pollinated species. Brinjal (Solanum melongenum L.) is one major cross-pollinated crop which most important vegetables of the world and a huge prospect in Sri Lanka. Several brinjal landraces are being cultivated in Sri Lanka even though few brinjal varieties have been released by Department of Agriculture. A local brinjal cultivar, so-called ‘Plastic’, is also one of the popular cultivars being cultivated by farmers in the northern region, especially in Vanni area of Sri Lanka. This cultivar does not have a pure population in the farmer’s field and the farmers received the seed materials from unreliable sources. Regional Agriculture Research and Development Centre (RARDC), Kilinochchi has initiated a purification program of the plastic cultivar since the year of 2016. Randomized complete block design (RCBD) was used with five replicates. Recurrent selection and restricted open-pollination methods have been continued for five consecutive seasons with five lines to get a purified high-yielding brinjal cultivar. Originally developed five lines were advanced for three seasons and one line (number 5) was dropped out from the third season owing to its low yielding performance. While improving the population, yield evaluation was also made. Yield evaluation conducted in the fourth and the fifth seasons with the selected lines that indicated significant difference in their yield performances among these lines. Finally, two high performing uniform lines (Line number 02 and 03) with the yield more than 22 t/ha were generated. These two lines could be promoted as promising variety/s after conducting multi-locations trials.
Keywords: Landraces; Population improvement; Recurrent selection